Timing of nitrogen fertilization influences color and anthocyanin content of apple (Malus domestica Borkh. cv ‘Royal Gala’) fruits - De Angelis, Veronica (2011)
Different timings and methods of N application modify N dynamics in the plant and could have differential effects on fruit color. To evaluate this possibility, an experiment was conducted during three seasons in a ‘Royal Gala’/EM9 apple orchard. The treatments were: (a) soil N after harvest; (b) foliar N after harvest; and (c) soil N in spring. No nitrogen was applied to the control. HUE angle, lightness, percentage of coverage color, and anthocyanin concentration were determined in the fruit skin. Among the treatments that received fertilization, the postharvest treatments resulted in fruits with darker colorations, higher percentages of coverage color, and higher concentration of anthocyanins. These could be related, at least partly, to lower values of light interception by the canopy, in comparison to the spring treatment. Our results suggest that the negative effects of N on fruit coloration can be mitigated by differing N application to the postharvest period.